A Study of Geographically Exogenic and Endogenic Forces in India: An Investigation into the Influence of Geomorphic Processes on Land Forms in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Geomorphic processes can create land forms. The endogenic forces (internal) and exogenic forces (external) are the two main types of geomorphic processes which results in earth movements. This paper studies about endogenic and exogenic forces in India.